New developments in systemic therapy for advanced biliary tract cancer - Morizane, Chigusa; Ueno, Makoto; Ikeda, Masafumi; Okusaka, Takuji; Ishii, Hiroshi; Furuse, Junji (Japanese journal of clinical oncology, 2018)
Biliary tract cancer, carcinoma of the extrahepatic bile ducts, carcinoma of the gall bladder, ampullary carcinoma and intrahepatic cholangiocarcinoma are often identified at an advanced stage and have poor prognoses. Although effective chemotherapy regimens are needed, their development remains unsatisfactory. From the results of a phase III clinical trial (ABC-02 trial), gemcitabine plus cisplatin is the standard first-line chemotherapeutic regimen for advanced biliary tract cancer. A phase III trial of gemcitabine plus cisplatin vs. gemcitabine plus S-1 therapy (FUGA-BT) demonstrated the non-inferiority of gemcitabine plus S-1 to gemcitabine plus cisplatin. A phase III trial of gemcitabine plus cisplatin vs. gemcitabine plus cisplatin plus S-1 (MITSUBA) was conducted, and the report on the results of the final analysis is being awaited. A standard second-line chemotherapeutic regimen has not yet been established. Fluoropyrimidines are frequently used in clinical practice. Despite many clinical trials being conducted with molecular targeted agents including erlotinib, cetuximab, panitumumab, bevacizumab, sorafenib, cediranib, trametinib and vandetanib, no agent has shown to be effective for advanced biliary tract cancer. Next-generation sequencing shows great promise by allowing rapid mutational analysis of multiple genes in human cancers, and attractive driver genetic alterations have been reported in biliary tract cancer. FGFR2 fusion gene, mutations of IDH1/2, BRAF, BRCA1/2, ATM, PIK3CA and overexpression of c-MET and HER2/neu are reported relatively frequently and are interesting targets. Therefore, future development in precision medicine utilizing next-generation sequencing is expected. Although the efficacy of immune checkpoint inhibitors, such as anti-PD-1, anti-PD-L1 and anti-CTLA4 antibodies, remains unknown at present, basic data and results of ongoing clinical trials are anticipated.